Etika, Moral, dan Akhlak di Era Digital: Tantangan dan Penerapan pada Masyarakat Modern - Wulandari, Dina Novita; Retnaningtyas, Yulia Fajar; Sarahdiba, Najwa Nisya; Ledysta, Claravia; Almahi, Neila Narani; Mauhub, Zahwa Azmi; Al Aziz, Maulana Muhammad Zakariyya (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Singaperbangsa Karawang, 2025)
Digital transformation has brought significant changes to the lives of modern society, but has also raised serious challenges to the implementation of ethics, morals, and ethics. Social media and other online platforms have blurred the boundaries between the real and virtual worlds, providing space for interactions without geographical boundaries that on the one hand enrich, but also complicate the implementation of traditional ethical values. This article examines the differences and challenges of implementing ethics, morals, and ethics in the digital era characterized by anonymity and uncontrolled dissemination of information. The research method uses a literature study approach, which analyzes various literatures to explore changes in people's behavior in the digital context. The results of the study show that anonymity, the spread of hoaxes, cyberbullying, and privacy violations are the main challenges that test the implementation of ethical values ​​in cyberspace. In addition, rapid social change often makes people ignore moral values ​​in online interactions. This article recommends the importance of strengthening digital literacy education, making strict regulations and policies, strengthening the role of families and communities, and using technology responsibly that emphasizes moral responsibility, integrity, and social awareness to form a more ethical society in the digital era. A deeper understanding of digital ethics is expected to help address emerging challenges and build a more moral digital environment.